Japanese racial identities within US-Japan relations, 1853-1919 - Merida, Tarik (Edinburgh University Press, 2023)
Considers: Did race really matter? Racial ideology and political pragmatism in U.S.-Japan relations.
Keywords: Japanese -- Race identity.; Race relations -- Political aspects.; Japan -- Foreign relations -- 19th century.; United States -- Foreign relations -- Japan.; Japan -- Foreign relations -- 20th century.; Japan -- Foreign relations -- United States.; Japon -- Relations extérieures -- 19e siècle.; Japon -- Relations extérieures -- 20e siècle.; Japon -- Relations extérieures -- États-Unis.; POLITICAL SCIENCE / International Relations / General.; Diplomatic relations; Race relations -- Political aspects; Japan; United States; 1800-1999